Agriculture risk facing climate change in the Cuitzeo region of the state of Michoacan, Mexico - Ortiz-Paniagua, Carlos Francisco; Alcaraz Vera, Jorge Víctor; Hernández Santoyo, Agustín (Acta Universitaria, 2023)
Agriculture is one of the most sensitive sectors to the effects of climate change (CC), particularly in some Mexican regions. The aim of this research is to quantify the magnitude of the agricultural risk to CC and its spatial distribution in the Cuitzeo Region (CR) in Michoacan. The methodology used has three stages: 1) detection of the regional CC signal, 2) estimation of vulnerability, and 3) measurement of agricultural risk. The results show that increase in temperature has a trend on 63% of the region and the CC signal in 80% of the territory. The agricultural risk to CC is distributed heterogeneously and with different magnitude. It concludes indicating the elements that require attention to reduce vulnerability and to make something avoid trend to reduce rainfall in the water catchment areas of the region.